A high power density graphite negative electrode material and its production process

By introducing LTO intercalation additives into the negative electrode material of lithium-ion batteries, a stable lithium-ion channel is constructed, which solves the problem of insufficient lithium-ion migration rate in the prior art and achieves a significant increase in battery power density.

CN119170782BActive Publication Date: 2025-03-04青岛青北碳素制品有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411620346.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-04
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion batteries have limitations in improving power density. Traditional carbon-based negative electrode materials are difficult to build stable lithium-ion channels, resulting in insufficient migration rate of lithium ions.

Method used

Using 2,4,6-tribromobenzene-1,3,5-trinitrile and 1,3,5-triacetylene benzene as raw materials, Heck reaction was carried out under alkaline conditions to form a carbon-rich matrix, and then ethoxysilane structure was introduced under hydrochloric acid catalysis, and co-hydrolyzed with tetraethyl titanium to form a gel, capture lithium ions to form a titanium lithium composite containing silicone, and finally form an LTO intercalation additive through high-temperature carbonization to build a stable lithium ion channel.

Benefits of technology

By building a stable lithium ion channel, the migration rate of lithium ions is significantly improved, and the power density of the battery is thus improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a high power density graphite negative electrode material and a production process thereof, belonging to the technical field of lithium ion batteries. The components of the negative electrode material are: a conductive agent 1.5-2wt%, a structural aid 0.8-1.2wt%, an LTO intercalation additive 10-15wt%, a binder 5.8-6.4wt%, and the balance is battery-grade graphite powder; the LTO intercalation additive is made of 2,4,6-tribromobenzene-1,3,5-trinitrile and 1,3,5-triethynylbenzene by Heck reaction to form a compound with a two-dimensional organic carbon network structure, and then tetrakis (2-hydroxyethoxy) silane reacts with its residual cyano group to introduce an ethoxysilane structure, and is co-hydrolyzed with tetraethyl titanate and adsorbs lithium ions to form a titanium-lithium complex containing organic silicon composites, and finally, a lamellar carbide of lithium titanium spinel intercalation is formed, a stable lithium ion channel is formed in the negative electrode material, and the power density of the battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular, relates to a high-power density graphite negative electrode material and a production process thereof. Background Art

[0002] With the popularization of electronic devices and the development of electric vehicles, the demand for energy storage systems is growing. As the main energy supply device for these devices, the energy density and power density of batteries become decisive factors. High-power density batteries can meet the needs of fast charging and discharging, and are an indispensable part of modern applications, especially in the field of electric vehicles, where the volume energy density and power density of batteries are particularly stringent.

[0003] Although lithium-ion batteries have made significant progress, there are still some key problems with their negative electrode materials. Although traditional carbon-based negative electrode materials (such as graphite) are low-cost and have good cycle stability, they are limited in improving power density. In lithium-ion batteries, power density depends on the migration rate of lithium ions inside the battery. The faster the diffusion rate of lithium ions in the electrode material, the higher the current rate that the battery can achieve during the charging and discharging process, so that more power can be output in a shorter time. In the prior art, there are various methods to improve battery power density, such as refining the particle size of the negative electrode material, shortening the diffusion path of lithium ions, and accelerating the migration of lithium ions. For example, lithium titanium oxide (LTO), lithium phosphorus oxide, aluminum lithium oxide, etc. are used to dope or coat modified graphite to promote the migration of lithium ions. To a certain extent, it can play a role in improving power density, but the effect is limited. The main reason is that these promoting doping materials are difficult to construct stable lithium ion channels. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a high power density graphite negative electrode material and a production process thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high power density graphite negative electrode material, comprising the following components:

[0007] Conductive agent 1.5-2wt%, structural additive 0.8-1.2wt%, LTO intercalation additive 10-15wt%, binder 5.8-6.4wt%, and the balance is battery-grade graphite powder.

[0008] The LTO intercalation additive is prepared by the following method:

[0009] Step A1: 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide are mixed under dry nitrogen protection, the temperature is raised to 150-160° C., and stirred at 60-90 rpm. The mixture is refluxed at a constant temperature for 48-55 hours. After the reaction is completed, dimethylacetamide is removed by vacuum rotary evaporation. The substrate is washed with water and dried in vacuo to obtain a carbon-rich matrix;

[0010] Furthermore, the feed ratio of 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide is 10mmol:15mmol:35-40mg:15-25mg:0.1-0.13g:60-80mL. Under alkaline catalytic conditions, 2,4,6-tribromobenzene-1,3,5-trinitrile and 1,3,5-triethynylbenzene undergo Heck reaction to form a compound with a two-dimensional organic carbon network structure.

[0011] Step A2: premix the carbon-rich matrix and tetrahydrofuran, adjust the pH value to 3-4 with hydrochloric acid, control the temperature of the water bath to 40-50°C, apply 120-150rpm stirring, add tetrakis(2-hydroxyethoxy)silane to react for 1-1.3h, then add lithium acetate, tetraethyl titanate and deionized water for ultrasonic vibration for 20-30min, let stand for 24h, take the bottom precipitate and dry it to obtain a composite precursor;

[0012] Furthermore, the feed ratio of the carbon-rich matrix, lithium acetate, tetraethyl titanate, tetrakis(2-hydroxyethoxy)silane, tetrahydrofuran and deionized water is 10g:4mmol:5mmol:2-3mmol:25-30mL:10-20mL. Under the catalysis of hydrochloric acid, tetrakis(2-hydroxyethoxy)silane preferentially reacts with the cyanide group on the carbon-rich matrix and is loaded into the carbon-rich matrix. It is then co-hydrolyzed with tetraethyl titanate to form a gel. These gels adsorb and capture lithium ions to form a complex.

[0013] Step A3: cold isostatically pressing the composite precursor, calcining and carbonizing it in a nitrogen atmosphere, cooling it in the furnace, and then grinding and crushing it to obtain an LTO intercalation additive;

[0014] Furthermore, the isostatic pressing pressure is 35-40MPa, the carbonization temperature is 820-850℃, and the time is 6-7h. The carbon-rich matrix is ​​carbonized at high temperature to form lamellar carbides, and the lithium-titanium composite is sintered to form a lithium-titanium spinel phase attached to the inner wall of the carbide interlayer, forming a large number of channels that promote the migration of lithium ions.

[0015] Furthermore, the grinding fineness of the LTO intercalation additive is not less than 325 mesh, which is conducive to subsequent grinding and dispersion to construct a uniform and efficient lithium ion channel.

[0016] Preferably, the conductive agent is selected from conductive carbon black, which has excellent conductivity and effectively improves the conductivity of the negative electrode.

[0017] Preferably, the structural additive is selected from carbon nanotubes, which have a large number of microscopic pores and play a supporting role in the negative electrode material to form a large number of lithium ion channels.

[0018] A production process of a high power density graphite negative electrode material, specifically comprising the following steps:

[0019] Step S1: premixing a conductive agent, a structural additive, an LTO intercalation additive, a binder and a battery-grade graphite powder, adding N-methylpyrrolidone, mixing and grinding, and obtaining a negative electrode slurry;

[0020] Step S2: Scrape the negative electrode slurry onto the surface of the current collecting substrate and bake it at 120° C. for 10 h to solidify the negative electrode slurry to form a negative electrode material.

[0021] Beneficial effects of the present invention:

[0022] The invention is based on traditional graphite negative electrode materials and is compounded with an independently developed LTO intercalation additive, which plays a significant role in improving the power density of lithium batteries; the LTO intercalation additive is made of 2,4,6-tribromobenzene-1,3,5-trinitrile and 1,3,5-triethynylbenzene as raw materials, and a palladium catalyst is used to promote the Heck reaction under alkaline conditions to form a compound with a two-dimensional organic carbon network structure, that is, a carbon-rich matrix, and then under the catalysis of hydrochloric acid, tetrakis(2-hydroxyethoxy)silane reacts with the cyano group on the carbon-rich matrix to introduce an ethoxysilane structure into the two-dimensional plane of the carbon-rich matrix, and the ethoxysilane structure is co-hydrolyzed with tetraethyl titanate to form a gel, and the adsorption of the gel is utilized It has the ability to capture lithium ions and form a titanium-lithium complex containing organic silicon. Finally, the carbon-rich matrix is ​​carbonized at high temperature to form lamellar carbides. The lithium-titanium complex is sintered to form a lithium-titanium spinel phase attached to the inner wall of the carbide interlayer, that is, the LTO intercalation additive is formed. The lithium-titanium spinel phase intercalation constructs a large number of microscopic ion permeation channels, and the LTO structure is stable, which strengthens the microscopic channels and is conducive to the formation of stable lithium-ion channels. The lithium-titanium spinel phase on these channels promotes the migration of lithium ions in the channels by charge compensation and regulating point defects in the channels, thereby accelerating the embedding and de-embedding of lithium ions in the negative electrode, thereby effectively improving the power density of the battery. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1, preparation of high power density graphite negative electrode material, the specific implementation process is as follows:

[0025] (1) Preparation of LTO intercalation additives

[0026] Step A1: 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide are mixed under the protection of dry nitrogen, the temperature is raised to 150°C, stirring is applied at 60rpm, and the reaction is refluxed at a constant temperature for 55h, wherein the feed ratio of 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide is 10mmol:15mmol:35mg:25mg:0.1g:60mL. After the reaction is completed, dimethylacetamide is removed by reduced pressure rotary evaporation, and the substrate is washed with water and vacuum dried to obtain a carbon-rich matrix.

[0027] Step A2: Premix the carbon-rich matrix and tetrahydrofuran, adjust the pH value to 4 with hydrochloric acid, control the temperature in a water bath to 40°C, apply stirring at 120rpm, add tetrakis(2-hydroxyethoxy)silane to react for 1.3h, then add lithium acetate, tetraethyl titanate and deionized water for ultrasonic oscillation for 30min, wherein the feed ratio of the carbon-rich matrix, lithium acetate, tetraethyl titanate, tetrakis(2-hydroxyethoxy)silane, tetrahydrofuran and deionized water is 10g:4mmol:5mmol:2mmol:25mL:20mL, let stand for 24h, take the bottom precipitate and dry it to obtain a composite precursor.

[0028] Step A3: The composite precursor is formed by cold isostatic pressing at 35 MPa, transferred into an atmosphere furnace, calcined and carbonized at 820° C. in a nitrogen atmosphere for 7 hours, and ground and crushed after cooling in the furnace to control the fineness to be not less than 325 meshes to obtain an LTO intercalation additive.

[0029] (2) Preparation of negative electrode materials

[0030] Ingredients: measured by weight percentage, conductive agent 2wt%, BP2000 conductive carbon black is used in the implementation process; structural additive 0.8wt%, CNT105 carbon nanotubes are used in the implementation process; LTO intercalation additive 10wt%, which is self-made in this embodiment; binder 5.8wt%, industrial grade polyvinylidene fluoride is used in the implementation process, and the balance is battery-grade graphite powder supplemented to 100wt%, AGP-2L-P type raw material is used in the implementation process.

[0031] Step S1: Add the conductive agent, structural additive, LTO intercalation additive, binder and battery-grade graphite powder into a stirrer and premix at 600 rpm for 30 minutes, then add N-methylpyrrolidone and mix and grind, control the solid content of the slurry to 50%, and obtain the negative electrode slurry.

[0032] Step S2: Scrape the negative electrode slurry onto the surface of the current collecting substrate. Copper foil is used during the implementation process. The negative electrode slurry is baked at 120° C. for 10 hours to solidify into a negative electrode material.

[0033] Example 2, preparation of high power density graphite negative electrode material, the specific implementation process is as follows:

[0034] (1) Preparation of LTO intercalation additives

[0035] Step A1: 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide are mixed under the protection of dry nitrogen, the temperature is raised to 160°C, stirring is applied at 90rpm, and the reaction is refluxed at a constant temperature for 48h, wherein the feed ratio of 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide is 10mmol:15mmol:40mg:15mg:0.13g:80mL. After the reaction is completed, dimethylacetamide is removed by reduced pressure rotary evaporation, the substrate is washed with water and vacuum dried to obtain a carbon-rich matrix.

[0036] Step A2: Premix the carbon-rich matrix and tetrahydrofuran, adjust the pH value to 3 with hydrochloric acid, control the temperature in a water bath to 50°C, apply stirring at 150rpm, add tetrakis(2-hydroxyethoxy)silane to react for 1h, then add lithium acetate, tetraethyl titanate and deionized water for ultrasonic oscillation for 20min, wherein the feed ratio of the carbon-rich matrix, lithium acetate, tetraethyl titanate, tetrakis(2-hydroxyethoxy)silane, tetrahydrofuran and deionized water is 10g:4mmol:5mmol:3mmol:30mL:10mL, let stand for 24h, take the bottom precipitate and dry it to obtain a composite precursor.

[0037] Step A3: The composite precursor is formed by cold isostatic pressing at 40 MPa, transferred into an atmosphere furnace, calcined and carbonized at 850° C. for 6 h in a nitrogen atmosphere, and ground and crushed after cooling in the furnace to control the fineness to be not less than 325 mesh to obtain an LTO intercalation additive.

[0038] (2) Preparation of negative electrode materials

[0039] Ingredients: measured by weight percentage, conductive agent 1.5wt%, BP2000 conductive carbon black is used in the implementation process; structural additive 1.2wt%, CNT105 carbon nanotubes are used in the implementation process; LTO intercalation additive 13wt%, homemade in this embodiment; binder 6.4wt%, industrial grade polyvinylidene fluoride is used in the implementation process, and the balance is battery-grade graphite powder supplemented to 100wt%, AGP-2L-P type raw material is used in the implementation process.

[0040] Step S1: Add the conductive agent, structural additive, LTO intercalation additive, binder and battery-grade graphite powder into a stirrer and premix at 600 rpm for 30 minutes, then add N-methylpyrrolidone and mix and grind, control the solid content of the slurry to 50%, and obtain the negative electrode slurry.

[0041] Step S2: Scrape the negative electrode slurry onto the surface of the current collecting substrate and bake it at 120° C. for 10 h to solidify the negative electrode slurry to form a negative electrode material.

[0042] Example 3, preparation of high power density graphite negative electrode material, the specific implementation process is as follows:

[0043] (1) Preparation of LTO intercalation additives

[0044] Step A1: 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide are mixed under the protection of dry nitrogen, the temperature is raised to 155°C, stirring is applied at 90rpm, and the reaction is refluxed at a constant temperature for 52 hours, wherein the feed ratio of 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide is 10mmol:15mmol:40mg:15mg:0.12g:75mL. After the reaction is completed, dimethylacetamide is removed by reduced pressure rotary evaporation, and the substrate is washed with water and vacuum dried to obtain a carbon-rich matrix.

[0045] Step A2: Premix the carbon-rich matrix and tetrahydrofuran, adjust the pH value to 3 with hydrochloric acid, control the temperature in a water bath to 40°C, apply stirring at 150 rpm, add tetrakis(2-hydroxyethoxy)silane to react for 1.1 h, then add lithium acetate, tetraethyl titanate and deionized water for ultrasonic oscillation for 25 min, wherein the feed ratio of the carbon-rich matrix, lithium acetate, tetraethyl titanate, tetrakis(2-hydroxyethoxy)silane, tetrahydrofuran and deionized water is 10 g: 4 mmol: 5 mmol: 3 mmol: 28 mL: 15 mL, let stand for 24 h, take the bottom precipitate and dry it to obtain a composite precursor.

[0046] Step A3: The composite precursor is formed by cold isostatic pressing at 35 MPa, transferred into an atmosphere furnace, calcined and carbonized at 850° C. for 6.5 h in a nitrogen atmosphere, and ground and pulverized after cooling in the furnace to control the fineness to be not less than 325 mesh to obtain an LTO intercalation additive.

[0047] (2) Preparation of negative electrode materials

[0048] Ingredients: measured by weight percentage, conductive agent 1.8wt%, BP2000 conductive carbon black is used in the implementation process; structural additive 0.9wt%, CNT105 carbon nanotubes are used in the implementation process; LTO intercalation additive 15wt%, which is self-made in this embodiment; binder 6.2wt%, industrial grade polyvinylidene fluoride is used in the implementation process, and the balance is battery-grade graphite powder supplemented to 100wt%, AGP-2L-P type raw material is used in the implementation process.

[0049] Step S1: Add the conductive agent, structural additive, LTO intercalation additive, binder and battery-grade graphite powder into a stirrer and premix at 600 rpm for 30 minutes, then add N-methylpyrrolidone and mix and grind, control the solid content of the slurry to 50%, and obtain the negative electrode slurry.

[0050] Step S2: Scrape the negative electrode slurry onto the surface of the current collecting substrate and bake it at 120° C. for 10 h to solidify the negative electrode slurry to form a negative electrode material.

[0051] Comparative Example 1

[0052] This comparative example refers to Example 3, except that no LTO intercalation additive is added, and battery-grade graphite powder is used to supplement the mixture to 100 wt %, and the rest of the implementation process is exactly the same.

[0053] Comparative Example 2

[0054] This comparative example refers to Example 3, except that the LTO intercalation additive is replaced with LTO coated graphite at the same weight ratio, and the rest of the implementation process is exactly the same, wherein the specific implementation process of LTO coated graphite is as follows:

[0055] Step B1: Tetrabutyl titanate and lithium acetate are mixed and added, anhydrous ethanol is added and mixed, then battery-grade graphite powder is added and mixed, the temperature is raised to 70° C., and stirred at 120 rpm for 2 h, and then evaporated to dryness to obtain a precursor;

[0056] Step B2: The precursor is transferred into an atmosphere furnace, calcined and carbonized at 750° C. in a nitrogen atmosphere for 10 h, and then broken up after cooling to obtain LTO-coated graphite.

[0057] Lithium iron phosphate, conductive carbon black and polyvinylidene fluoride were mixed in a mass ratio of 92:2:6, N-methylpyrrolidone was added and mixed and ground, and the solid content of the slurry was controlled to be 50% to obtain a positive electrode slurry, which was then coated on the surface of a copper foil and baked at 120°C for 10 hours to prepare a positive electrode material; the positive electrode material and the negative electrode material were sliced, 1 mol / L LiPF6 was used as an electrolyte, Celgard 2300 was used as a separator, and they were stacked and assembled into an energy storage device in a sandwich structure;

[0058] The energy storage device assembled as above was subjected to charge and discharge test at 4C rate on CTE-4048-5V100A-NTA power cell tester. At the same time, electrochemical impedance test was performed using Parstat 4000A electrochemical workstation to detect volume energy density and volume power density of the energy storage device. The specific test results are shown in Table 1:

[0059] Table 1 Test results of volume energy density and volume power density

[0060] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 <![CDATA[Volume energy density / Wh·L -1 > 269.1 275.3 276.2 242.4 266.3 <![CDATA[Volume power density / W·L -1 > 44280.4 46853.5 47119.8 40255.7 41631.5

[0061] It can be seen from the test results in Table 1 that, under the same energy storage structure, the negative electrode material of the embodiment can obtain higher volume energy density and volume power density.

[0062] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0063] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high power density graphite negative electrode plate, characterized in that: It is formed by curing the current collecting substrate and the negative electrode slurry, and the negative electrode slurry is composed of the following components: 1.5-2wt% of conductive agent, 0.8-1.2wt% of structural additive, 10-15wt% of LTO intercalation additive, 5.8-6.4wt% of binder, and the balance is battery-grade graphite powder; The LTO intercalation additive is prepared by the following method: Step A1: 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide are mixed under the protection of dry nitrogen, the temperature is raised to 150-160° C., and the mixture is stirred and refluxed at a constant temperature for 48-55 hours. After the reaction is completed, dimethylacetamide is removed by vacuum rotary evaporation, and the substrate is washed with water and dried in vacuo to obtain a carbon-rich matrix; Step A2: premix the carbon-rich matrix and tetrahydrofuran, adjust the pH value to 3-4 with hydrochloric acid, control the temperature of the water bath to 40-50°C, stir and add tetrakis(2-hydroxyethoxy)silane to react for 1-1.3h, then add lithium acetate, tetraethyl titanate and deionized water for ultrasonic oscillation for 20-30min, let stand for 24h, take the bottom precipitate and dry it to obtain a composite precursor; Step A3: cold isostatically pressing the composite precursor, calcining and carbonizing it in a nitrogen atmosphere, cooling it in the furnace, and then grinding and crushing it to obtain an LTO intercalation additive; The structural additive is carbon nanotube.

2. A high power density graphite negative electrode sheet according to claim 1, characterized in that: The feed ratio of 2,4,6-tribromobenzene-1,3,5-trinitrile, 1,3,5-triethynylbenzene, bistriphenylphosphine palladium dichloride, cuprous iodide, potassium carbonate and dimethylacetamide is 10 mmol: 15 mmol: 35-40 mg: 15-25 mg: 0.1-0.13 g: 60-80 mL.

3. A high power density graphite negative electrode sheet according to claim 2, characterized in that: The feed ratio of the carbon-rich matrix, lithium acetate, tetraethyl titanate, tetrakis(2-hydroxyethoxy)silane, tetrahydrofuran and deionized water is 10 g: 4 mmol: 5 mmol: 2-3 mmol: 25-30 mL: 10-20 mL.

4. A high power density graphite negative electrode sheet according to claim 3, characterized in that: The pressure of cold isostatic pressing is 35-40MPa, the carbonization temperature is 820-850℃, and the carbonization time is 6-7h.

5. The high power density graphite negative electrode sheet according to claim 1, characterized in that: The grinding fineness of the LTO intercalation additive is not less than 325 mesh.

6. The high power density graphite negative electrode sheet according to claim 1, characterized in that: The conductive agent is conductive carbon black.

7. A production process for a high power density graphite negative electrode sheet according to any one of claims 1 to 6, characterized in that: Including the following processes: Step S1: premixing a conductive agent, a structural additive, an LTO intercalation additive, a binder and a battery-grade graphite powder, adding N-methylpyrrolidone, mixing and grinding, and obtaining a negative electrode slurry; Step S2: Scrape the negative electrode slurry onto the surface of the current collecting substrate, bake at 120° C. for 10 h, and solidify the negative electrode slurry to form a negative electrode sheet.

Citation Information

Patent Citations

  • Preparation process of low-temperature graphite negative electrode material

    CN117985707A

  • Graphite alkene combined electrode

    CN205140537U